PENGEMBANGAN BAHAN AJAR POKOK BAHASAN HIDROLISIS GARAM YANG DIOLAH DENGAN EMPAT TAHAP PENGOLAHAN BAHAN AJAR - sulisnawati, lilis (2014)
This study, entitled "Development of Instructional Materials on Salt Hydrolysis Subject which are processed with Four Stages of Teaching Materials Processing" this aims to develop teaching materials subject hydrolysis of salts with four stages of processing materials, and then determine the response of students and teachers towards teaching materials have been developed that. The method used in this research is the Research and Development, the study was conducted only at the stage of product trials. The subject of this study is instructional materials on salt hydrolysis subject that have been processed with four stages of teaching materials processing. The results showed that: 1) Processing the teaching materials on salt hydrolysis subject made through 4 stages, includes the stages of selection, structuring, characterization, and didactic reduction through use level of historical development, image of the experimental results, illustration with image, table, explanation with example, explanation with example questions, and generalizations, 2) readability the teaching materials on salt hydrolysis subject that have been developed is relatively high in a category with a percentage of 65%, 3) teacher perceptions about the appropriateness of nstructional materials on salt hydrolysis subject that have been developed, indicating that these teaching materials have good criteria.-------- Skripsi yang berjudul "Pengembangan Bahan Ajar Pokok Bahasan Hidrolisis Garam yang Diolah dengan Empat Tahap Pengolahan Bahan Ajar" ini bertujuan untuk mengembangkan bahan ajar pokok bahasan hidrolisis garam dengan empat tahap pengolahan bahan ajar, kemudian mengetahui tanggapan siswa dan guru terhadap bahan ajar yang telah dikembangkan tersebut. Metode yang digunakan dalam penelitian ini adalah metode Penelitian dan Pengembangan (Research and Development), pada penelitian ini dilakukan hanya sampai pada tahap uji coba produk. Subjek penelitian berupa bahan ajar hidrolisis garam yang telah diolah dengan Empat Tahap Pengolahan Bahan Ajar. Hasil penelitian menunjukkan bahwa: 1) Pengolahan bahan ajar hidrolisis garam dilakukan melalui 4 tahap, yaitu tahap seleksi, strukturisasi, karakterisasi, dan reduksi didaktik berupa penggunaan tingkat perkembangan sejarah, gambar hasil percobaan, ilustrasi dengan gambar, tabel, penjelasan dengan contoh, penjelasan dengan contoh soal, dan generalisasi, 2) Keterbacaan bahan ajar hidrolisis garam yang telah dikembangkan ini tergolong ke dalam kategori tinggi dengan persentasi 65%, 3) Persepsi guru tentang kelayakan bahan ajar hidrolisis garam yang telah dikembangkan, menunjukkan bahwa bahan ajar tersebut memiliki kriteria baik